Web-based decision support system for boarding house selection according to preferences in Kefamenanu (BTN) area using Tsukamoto Fuzzy Logic Method - Chandra, Rudy; Kelen, yoseph Pius Kurniawan; Manek, Patricia Gedrudis; Septian Manek, Siprianus (Jurnal Simantec, 2025)
The problem in searching for boarding houses in the Kefamenanu (BTN) area is the many choices with different variations in price, facilities, distance, and comfort levels, making it difficult for prospective residents to determine a boarding house that suits their personal preferences. This study aims to build a web-based decision-making system that can help users choose a boarding house according to their interests quickly and accurately. The method used is the Tsukamoto Fuzzy Logic method, which is able to accommodate uncertainty and subjectivity in the assessment process of boarding house selection criteria. The system is designed with several fuzzy variables such as price, distance, facilities, and comfort, which are processed through fuzzy rules in the form of IF-THEN to produce the best boarding house recommendations. The novelty of this study lies in the application of the Tsukamoto method in the context of selecting boarding houses in Kefamenanu, which has not previously been widely developed using a fuzzy logic approach. The contribution of this study is to produce a web-based platform that is able to accelerate the process of searching for boarding houses that suit user needs, while increasing accuracy and satisfaction in decision making. The results of the study showed that the system was able to recommend boarding house options with a level of user preference matching reaching 90%, based on the results of trials on 30 respondents in the BTN Kefamenanu area.Keywords: Web-Based Application, Fuzzy Logic, Tsukamoto Method, Boarding House Selection, Decision Support System